Respiratory responses during and after arm pulling ergometer work - Witt, M.; Neumann, G.; Berbalk, A. (Biomechanics and Medicine in Swimming IX, 2003)
INTRODUCTION In swimming spiroergometry cannot be used in routine tests. That´s why tests under special conditions in swimming flume or pool are used (e.g. Keskinen et al./ 2001). Also the application of the re-breathing method represents a possible alternative (Reer et al./ 1999). In our opinion the informative value of the re-breathing method is strongly limited by the absence of a strict coupling of respiration and movement because of the post load phase. Significant deviations in O2 and CO2 concentration in expired air during breath by breath-monitoring require an integration over several breathes. This is in contradiction to the high dynamics of the spirometric parameters in the post load phase. In our study we simulated swimming arm movements in a dry-land arm ergometer (swim bench typ) test under semi-specific conditions. Thus the purpose of this study was to investigate into the relation between spirometric parameters during and after pulling exercise. METHODS 23 national team tri-athletes performed an all out test lasting five minutes on an arm pulling ergometer. During the test all spirometric data were registered online for the whole test and one minute during the post load phase. In addition the subjects performed two step tests in cycling and running and one VO2max-test in running. RESULTS Athletes reached almost the same blood lactate concentration but lower oxygen consumption on the rope pulling ergometer when compared with the other tests. This is an indication of a high demand for the anaerobic metabolism. Large parts of relatively unloaded muscles cannot compensate acidosis any longer. However, a correlation between oxygen consumption during rope pulling and calculation of oxygen based on the post load phase if collection starts later than 10 s after the end of test was not found. DISCUSSION Problems in gas analyses in swimming make complicate comparative investigations in tri-athletes. According to these experiments a high correlation between breathing parameters and cyclic movements during semi-specific dry-land test as well as in pool swimming was found. This test procedure is suitable for the specific evaluation of upper extremities muscles` metabolism.